Anatomic description of Peyer's patches in the small intestine of the alpaca (Vicugna pacos) - Flores M., Jimmy (2020)
The small intestine of 10 apparently healthy adult alpacas was collected in the municipal slaughterhouse of Huancavelica, Peru to describe the anatomical characteristics of Peyer's patches. The highest number of Peyer's patches was observed in the jejunum, followed by the duodenum and ileum (p<0.05), but the highest density was observed in the ileum (p<0.05). There were no significant differences by effect of the sex of the animals. The location with reference to the transverse plane of the intestine was 65.88% on the anti-mesenteric border, 27.87% on the lateral border and 11.40% on the mesenteric border (p<0.05). No clear pattern of distribution with reference to the longitudinal plane was found, except at the level of the ileal valve (2-3 cyst shape Peyer's patches bordering the ileal ring.) Several forms of presentation were observed: the nodular form in the duodenum and jejunum, faviform form in jejunum, cup shape in jejunum, ileum and sporadically in duodenum, and cyst shape, the most prominent, in the distal portions of the ileum. In addition, two intermediate forms were observed: nodular-cup and cup-faviform. It is concluded that the alpaca presents peculiar characteristics in the Peyer's patches different from other domestic species.